Compact neutron source from head-on collision of high energy density plasma jets - Cui, Ye; Ke, Yan-Zhao; Yang, Xiao-Hu; Ma, Yan-Yun; Shao, Fu-Qiu (Frontiers in Physics, 2022)
We propose a new scheme to generate a neutron source with a short duration, and the scheme is validated in two-dimensional radiation hydrodynamic simulations. When a laser beam irradiates a deuterated polystyrene cone with a half-opening angle of 60°, high energy density plasma jets are produced due to the converging effect. As two laser-driven counter-propagating jets collide in a head-on configuration, the kinetic energy converts into internal energy efficiently, inducing a significant increase in density and temperature. Then, deuteron–deuteron thermonuclear reactions are triggered, and plenty of neutrons are released. The simulation results show that the total neutron yield is as high as 6.6×108 with a duration of 103 ps, providing a new way to achieve ultrafast diagnosis with high resolution in experiments.